PEOPLE WITH DISABILITIBS AND NATURE TOURISM: A SOUTH AFRICA CASE STUDY - Dippenaar, Stephanie; Kotze, Nico (Social Work/Maatskaplike Werk, 2005)
Almost seven percent of the total population of South Africa are disabled, according to Statistics South Africa. Of this group, 21% are physically disabled. A lack of recreational opportunities is listed as one of the major sources of stress for this group. The accessibility of parks and reserves in the Limpopo Province for wheelchair-bound people is investigated in this case study. The province has a rich natural heritage as well as an abundance of wilderness areas, and although ecotourism already plays an important role in the economic development of the province, it is still under-utilised. Given the absence of rain and the moderate temperature in winter, the Limpopo Province is one of the most suitable in South Africa for outdoor recreational activities during the winter months. To evaluate parks and reserves in the province in terms of their accessibility to people with disabilities, especially those confined to wheelchairs, a model was developed with a set of criteria against which tourism venues could be tested. Values ranging from 3 for full accessibility to O for total inaccessibility were allocated and used to evaluate the parks and reserves in the study area. An average value was calculated for each venue. These averages were finally tested against the accessibility index to determine the extent to which the park or reserve is accessible to people with disabilities.